2010
DOI: 10.1248/jhs.56.733
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Gene Expression Levels of Mevalonate Pyrophosphate Decarboxylase between Stroke-prone Spontaneously Hhypertensive and Wistar Kyoto Rats

Abstract: The relationship between protein and mRNA levels of mevalonate pyrophosphate decarboxylase (MPD) in rat tissues remains to be clarified. In this study, we examined the distribution of the mRNA in Wistar rat tissues by real-time PCR. When the relative expression of MPD in 1 mg of tissue was quantified using glyceraldehyde-3-phosphatedehydrogenase (GAPDH) as an internal control, the mRNA level was found to be markedly higher in the spleen and liver than in other organs. The correlation coefficient between protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…34) We also reported that MPD mRNA levels in the liver were lower in SHRSP than in WKY. 35) These findings indicated that the reduced expression of MPD could be attributed to two causes. Low MPD mRNA levels in the livers of SHRSP may be caused by (1) a post-transcriptional effect (accelerated mRNA degradation or inhibited translation from mRNA to protein) or (2) reduction in the expression of heterogeneous nuclear RNA (hnRNA) at the transcriptional level.…”
mentioning
confidence: 94%
“…34) We also reported that MPD mRNA levels in the liver were lower in SHRSP than in WKY. 35) These findings indicated that the reduced expression of MPD could be attributed to two causes. Low MPD mRNA levels in the livers of SHRSP may be caused by (1) a post-transcriptional effect (accelerated mRNA degradation or inhibited translation from mRNA to protein) or (2) reduction in the expression of heterogeneous nuclear RNA (hnRNA) at the transcriptional level.…”
mentioning
confidence: 94%
“…We have also previously shown that relative mRNA levels of IPI, SQS, LSS, sterol‐C5‐desaturase (SC5D), and 7‐dehydrocholesterol reductase (DHCR7) in the liver of SHRSP were the same as those in WKY . Further, the relative mRNA and protein levels of MPD and SQE were lower in the liver of SHRSP than in WKY . Anderson et al reported a correlation coefficiency of 0.48 between the abundance of mRNA and protein as determined by transcriptome and proteome analysis, suggesting that post‐transcriptional regulation of gene expression is a frequent phenomenon in higher organisms.…”
Section: Introductionmentioning
confidence: 90%
“…17 Further, the relative mRNA and protein levels of MPD and SQE were lower in the liver of SHRSP than in WKY. [18][19][20][21] Anderson et al 22 reported a correlation coefficiency of 0.48 between the abundance of mRNA and protein as determined by transcriptome and proteome analysis, suggesting that post-transcriptional regulation of gene expression is a frequent phenomenon in higher organisms. Because it cannot be concluded that decreased cholesterol synthesis is caused by the reduction of the abovementioned mRNA levels alone, an evaluation of protein levels and enzymatic activity is required.…”
mentioning
confidence: 99%
“…20) We also reported that MPD mRNA levels in the liver were lower in SHRSP than in WKY. 21) Furthermore, we found that reductions in MPD expression levels in the livers of SHRSP were suggested to be controlled by the upregulation of microRNA (miR)-214 and downregulation of transcriptional levels. 22) miR was shown to reduce protein levels by inhibiting its synthesis from mRNA or accelerating the degradation of mRNA.…”
Section: 2)mentioning
confidence: 95%